Cyclones and Vortices: Alejo Carpentier's Reasons of State as Cartesian Discourse - Joseph F. O'Neill (Studies in 20th & 21st Century Literature, 1978)
Alejo Carpentier's Reasons of State is a reconstruction of Cartesian discourse that is paradoxically both fantastic and baroque in its implications. Building upon the assumption that Cartesianism is typically baroque and therefore a dynamism, rather than a dichotomy of subject and object, the novel proceeds in the form of a retrospective deathbed narrative to suggest the radically anti-Cartesian polarization of subject and object in fin de siècle Latin America by portraying its dictator/narrator as a man whose world-view, like his culture's, is schizophrenically divided between magical realism and positivist progressivism. This ambiguous narrative perception is comparable to that of the literary genre known as the fantastic, whose several subjective themes are found to be operative in Reasons of State. Their working-out in the novel, however, is not exclusively psychological or socio-psychological. Ultimately they assume in the narrator's retrospective reflections a metaphorical character that effects a paradoxical synthesis of the prevailing opposed epistemologies: a self-aware folk consciousness that, in its dependence upon contradiction, is indisputably baroque.
Keywords: Alejo Carpentier; Reasons of State; Cartesian discourse; Cartesianism